Globalization and the Labour Movement - Schmidt, Ingo (Labour / Le Travail, 2009)
The article reviews and comments on the books, "European Unions: Labor's Quest for a Transnational Democracy," by Roland Erne, "The Struggle for a Social Europe: Trade Unions and EMU in Times of Global Restructuring," by Andreas Bieler, and "Labour and the Challenges of Globalization: What Prospects for Transnational Solidarity?," by Andreas Bieler, Ingemar Lindberg, and Devan Pillay.
Keywords: BIELER, Andreas; BOOKS -- Reviews; ERNE, Roland; EUROPEAN Unions: Labor's Quest for a Transnational Democracy (Book); LABOUR & the Challenges of Globalization: What Prospects for Transnational Solidarity? (Book); LINDBERG, Ingemar; Nonfiction; PILLAY, Devan; STRUGGLE for a Social Europe: Trade Unions & EMU in Times of Global Restructuring, The (Book)